An Assessment of Local Economic Empowerment Using Halal Tourism Approach: A Case from Sembalun District East Lombok, Indonesia - Ima Rahmawati Sushanti; Mustamin H. Idris; Baiq Harly Widayanti; Fariz Primadi Hirsan; Lukman Abdullah; Intan Savia Fitri (Universitas Muhammadiyah Mataram, 2018)
This study aimed to assess the local economic empowerment based on halal principles in Sembalun, a village within the circumference of Rinjani, the newly-designated world geopark by UNESCO. The descriptive qualitative method was chosen to analyze the data. The Participatory Rural Appraisal was used as an instrument to identify the expectations of the economy of local community. The study showed that local economic empowerment could be developed in several ways as follows: 1) Halal food initiative through increasing community participation and skills, involving institutions, providing intensive assistance, and increasing the role of community and institution in creating cooperation; 2) Worship facility improvement through increasing quality and maintenance of available worship facilities; 3) Services during Ramadan by improving the community and institutional capacity as well as delivering information to tourism operators and visitors; 4) Supporting facilities upgrading through increasing the numbers of water-friendly toilets both in quantity and quality; 5) Halal activities enrichment by eliminating non-halal activities and promote halal activities only; 6) Privacy leisure facilities and services provision through increasing institutional and community capacity in providing privacy leisure facilities and services as well as developing cooperation with stakeholders.